Effects of the Occupational Safety and Health Administration's control of hazardous energy (lockout/tagout) standard on rates of machinery-related fatal occupational injury. Issue 5 (4th October 2007) - Bulzacchelli, Maria T; Vernick, Jon S; Webster, Daniel W; Lees, Peter S J
Abstract : Objective: To evaluate the impact of the United States' federal Occupational Safety and Health Administration's control of hazardous energy (lockout/tagout) standard on rates of machinery-related fatal occupational injury. The standard, which took effect in 1990, requires employers in certain industries to establish an energy control program and sets minimum criteria for energy control procedures, training, inspections, and hardware. Design: An interrupted time-series design was used to determine the standard's effect on fatality rates. Machinery-related fatalities, obtained from the National Traumatic Occupational Fatalities surveillance system for 1980 through 2001, were used as a proxy for lockout/tagout-related fatalities. Linear regression was used to control for changes in demographic and economic factors. Results: The average annual crude rate of machinery-related fatalities in manufacturing changed little from 1980 to 1989, but declined by 4.59% per year from 1990 to 2001. However, when controlling for demographic and economic factors, the regression model estimate of the standard's effect is a small, non-significant increase of 0.05 deaths per 100 000 production worker full-time equivalents (95% CI −0.14 to 0.25). When fatality rates in comparison groups that should not have been affected by the standard are incorporated into the analysis, there is still no significant change in the rate of machinery-related fatalities in manufacturing. Conclusions: There is no evidence that the lockout/tagout standard decreased fatality rates relative to other trends in occupational safety over the study period. A possible explanation is voluntary use of lockout/tagout by some employers before introduction of the standard and low compliance by other employers after.